ACM as a pathway to mitigate Jakarta's flood impacts in a changing climate - Kusumanto, T.; Surtiari, G.A.K.; Zevenbergen, C.; Triyanti, A.; Samsura, D.A.A.; Moeliono, T.P.; Budiyono, Y. (Routledge, 2023)
This chapter assesses ACM’s potential as a pathway to address the flooding problem of Greater Jakarta, significantly exacerbated by land subsidence and climate change. It is based on a thought experiment by the authors to envision application of this approach to the problem and is not the result of empirical work. A background of Jakarta’s flooding is first provided and subsequently its framing as a ‘wicked problem’. Results of the thought experiment are then discussed, focusing on three questions: (i) Can ACM be applied, given Jakarta’s flooding governance structure? (ii) Will ACM’s social learning work for the flooding problem? And (iii) if ACM were applicable to Jakarta’s case, what operational indicators would apply? The chapter concludes with recommending a two-step ACM pathway: (1) adjusting the current flooding governance structure, for which leadership is needed with a long-term vision and the application of adaptive governance at the river basin scale; (2) shaping the enabling conditions for learning that stimulate creativity in and discovery of new problem framings and solutions outside the policy system. While the authors recognise the considerable challenges when applying ACM to the flooding of Greater Jakarta, the crisis stage it has reached necessitates adaptation approaches that can break the cycle of narrow, longstanding paradigms, policy beliefs, and maladaptive pathways.